AN ANALYSIS OF SELLERS’ AND BUYERS’ SPEECH ACTS IN DAILY TRANSACTIONAL COMMUNICATION AT BANYUASRI TRADITIONAL MARKET IN BULELENG - Padmayanti, D.R; Wedhanti, N.K; Agustini, D.A.E (Universitas Pendidikan Ganesha, 2018)
This research aimed to analyze the forms and functions of speech acts that were found in daily transactional communication between sellers and buyers in Banyuasri traditional market. This research was descriptive qualitative approach since the main focus is about describing and explaining the phenomenon of speech acts that are used by sellers and buyers, the forms and also the functions of speech acts in the daily routines speech at market environment. The subjects of this research were 10 sellers and 10 buyers at Banyuasri traditional market. The data gathered were analyzed by using Miles and Huberman model, namely, collecting data, data reduction, data display and conclusion drawing. The result of the data shows the form of speech act mostly uses by the sellers and buyers at Banyuasri traditional market is representative illocutionary acts.